Diferencias entre la Contabilidad tradicional del sector público vs las Normas Internacionales de Contabilidad del sector público en Colombia con proyecciones de impacto de este sector - Avendaño Martínez, Juliana (Ciencias Administrativas, Económicas y Contables, 2018)
The conversion of International Accounting Standards to Colombian Standards is a subject that has undergone a major change in the accounting sector due to the new procedures required by the IASC, that explains than only 10% of Colombia companies have implemented international accounting rules for 2016, and it is understood that in the same year all Colombian companies would have adopted those standards. Most of enterprises that adopted this measure are those classified as PLENAS. Which represents only 10 per cent of Colombian economy, all the rest, 90 per cent are companies classified as PYMES (Portfolio 2006) that are in the conversion process for this year. Public sector in Colombia included in the Colombian standard has been treated in a different manner in front of private sector what explains the existence of a plan of accounts for the public sector, a public accounting system, and special regulations for this sector, since in the administration of public resources the demand and control of accounting information is greater than accounting in the private sector, Both the public sector has a challenge to the international .regulations since there is little time for adoption and the same rules regarding the transparency and integrity of accounting information must be preserved